An adventure in space and time : [with bonus DVD : An unearthly child] [videorecording (Blu-Ray)] - Gatiss, Mark; Bradley, David, 1942-; Raine, Jessica, 1982-; Dhawan, Sacha; Manville, Lesley; Cox, Brian, 1946- (Doctor Who (Series), 2014)
An adventure in space and time: Actor William Hartnell felt trapped by a succession of tough-guy roles. Wannabe producer Verity Lambert was frustrated by the TV industry's glass ceiling. Both of them were to find unlikely hope and unexpected challenges in the form of a Saturday afternoon drama, time travel and monsters! Allied with a brilliant creative team, they went on to introduce the world to the longest running science fiction series ever, currently in its 50th year and counting.